2021
DOI: 10.1177/20587384211038357
|View full text |Cite
|
Sign up to set email alerts
|

Insulin amyloid fibrils interact directly with the NLRP3, resulting in inflammasome activation and pyroptotic cell death

Abstract: Introduction Nucleotide-binding oligomerization domain-like receptor family, pyrin domain containing 3 (NLRP3), an intracellular pattern recognition receptor, recognizes various pathogen-associated molecular pattern and/or damage-associated molecular pattern molecules to constitute inflammasome that act as an interleukin (IL)-1β processing platform. Injected insulin is reported to induce focal amyloidosis and the formation of subcutaneous lumps called insulin balls, but the formation of subcutaneous lumps and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Because we reported previously that IAPP, Aβ, and insulin amyloid fibrils interact directly with the NLRP3 inflammasome, 20 22 we thought that B2M might also interact with NLRP3 to support formation of amyloid fibrils. As expected, we observed a high ALPHA signal for NLRP3-Btn plus B2M amyloid fibrils ( Figure 2(b) ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Because we reported previously that IAPP, Aβ, and insulin amyloid fibrils interact directly with the NLRP3 inflammasome, 20 22 we thought that B2M might also interact with NLRP3 to support formation of amyloid fibrils. As expected, we observed a high ALPHA signal for NLRP3-Btn plus B2M amyloid fibrils ( Figure 2(b) ).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, we reported that Aβ, IAPP, and insulin amyloid fibrils interact directly with NLRP3 and activate the NLRP3 inflammasome. 20 22 A recent report suggests that B2M acts as a driver that initiates inflammatory responses by myeloma-associated macrophages, the process of which depends on activation of the NLRP3 inflammasome after B2M accumulation in these cells. 23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Нарушения синтеза и биогенеза инсулина приводят к развитию диабета и необходимости для пациентов прибегать к регулярным и многочисленным инъекциям препаратов инсулина. Известно, что инсулин может агрегировать с образованием фибриллярных структур [1][2][3][4][5][6], в том числе в местах инъекций [1,7,8], образуя амилоиды и вызывая такую патологию как инъекционный инсулиновый амилоидоз, в значительной степени снижающий эффективность терапии [1]. Следует отметить, что способность фибриллизоваться in vitro описана в литературе для разных типов инсулина [1][2][3][4][5][6].…”
Section: Introductionunclassified
“…Известно, что инсулин может агрегировать с образованием фибриллярных структур [1][2][3][4][5][6], в том числе в местах инъекций [1,7,8], образуя амилоиды и вызывая такую патологию как инъекционный инсулиновый амилоидоз, в значительной степени снижающий эффективность терапии [1]. Следует отметить, что способность фибриллизоваться in vitro описана в литературе для разных типов инсулина [1][2][3][4][5][6]. Однако условия, в которых авторы этих работ проводили инкубацию, такие как рН среды, длительность и температура, не дают возможности ответить на вопрос каковы механизмы фибриллизации инсулина после инъекций in vivo.…”
Section: Introductionunclassified